Hubungan Pengetahuan dan Pola Asuh Orang Tua tentang Gizi Seimbang dalam Pencegahan Gizi Kurang pada Balita - Sihite, Helprida; Sinaga, Mega Silvia; Mayes Felda Simamora (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to examine the relationship between parental knowledge and parenting styles regarding balanced nutrition in preventing malnutrition among toddlers in Pasingguran 1 Village, Pollung Subdistrict, Humbang Hasundutan Regency. This research utilized a descriptive-analytic method with a cross-sectional approach, involving 31 respondents. The results showed a significant relationship between parental knowledge and the prevention of malnutrition (p-value < 0.05) as well as between parenting styles and the prevention of malnutrition (p-value < 0.05). The study concludes that good knowledge and supportive parenting styles significantly influence efforts to prevent malnutrition among toddlers. Therefore, improving parental knowledge and appropriate parenting practices should be a primary focus in health interventions to reduce the prevalence of malnutrition in the region.